(untitled) (AYUSHDHARA, 2025)
Trigeminal neuralgia, also known as Tic Douloureux, is a condition characterized by unilateral, lancinating facial pain affecting the branches of the trigeminal nerve. Clinically, it manifests as excruciating paroxysms of pain localized in the lips, gums, cheeks, or chin. While trigeminal neuralgia is predominantly idiopathic, it is also indicative of action potentials in pain-sensitive fibers of the fifth cranial nerve root before it enters the brainstem. Case: A 39-year-old male patient presented with left-sided facial pain persisting for two years at the Government Ayurveda College and Hospital, Nagpur. The pain was predominantly distributed across the left cheek and chin, radiating towards the jaw region. The patient underwent Ayurvedic interventions for a duration of 2 months. Notable improvements were documented using the visual analogue scale (VAS) for pain and the hospital anxiety and depression scale (HADS). Observations from this case underscore the efficacy of Ayurvedic interventions in alleviating acute paroxysms of pain associated with classical trigeminal neuralgia and enhancing the overall quality of life for affected individuals. Present case was diagnosed as suffering from Anantavata, addressed through four sessions of leech therapy, alongside the administration of Ekangaveer Ras, Mahavatavindwas Rasa, Guduchi Stawa, Ashwagandha Churna, and Rajata Bhashma,with a local Panchakarma procedure.